1975
DOI: 10.1084/jem.141.1.42
|View full text |Cite
|
Sign up to set email alerts
|

The specificity of cellular immune responses in guinea pigs. I. T cells specific for 2,4-dinitrophenyl-o-tyrosyl residues.

Abstract: Responses of thymus-derived (T) lymphocytes to hapten-protein conjugates are very largely specific for carrier-and conjugate-specific determinants ; such responses rarely show the hapten specificity which predominates in the responses of thymus-independent bone marrow-derived (B) lymphocytes to similar antigens (1) . These findings, and similar observations in other antigen systems, have led to the suggestion that T and B cells have distinctive libraries of specific receptors, or perhaps very different require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

1975
1975
1984
1984

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
4
26
0
Order By: Relevance
“…These findings include the observations that: (a) H-2 homology is required between stimulator and target cells (10,11,13); (b) TNP-modified and NIP-AGG-modified stimulating cells generate clones of effectors which can distinguish between these two modifying agents (11); (c) cold target inhibition can occur only when the competing, nonradioactive target cells are both H-2-matched and modified with the same agent as the stimulating cells (11,13); and (d) inhibition of the lysis of modified target cells is obtained by anti-H-2 sera directed against the modified targets (16). Furthermore, the observations presented in this report are compatible with the results of Janeway and co-workers using related nitrophenyl compounds (3,4) in which specificity was shown to include both the nitrophenyl groups and part of the protein carrier.…”
Section: Discussionsupporting
confidence: 82%
“…These findings include the observations that: (a) H-2 homology is required between stimulator and target cells (10,11,13); (b) TNP-modified and NIP-AGG-modified stimulating cells generate clones of effectors which can distinguish between these two modifying agents (11); (c) cold target inhibition can occur only when the competing, nonradioactive target cells are both H-2-matched and modified with the same agent as the stimulating cells (11,13); and (d) inhibition of the lysis of modified target cells is obtained by anti-H-2 sera directed against the modified targets (16). Furthermore, the observations presented in this report are compatible with the results of Janeway and co-workers using related nitrophenyl compounds (3,4) in which specificity was shown to include both the nitrophenyl groups and part of the protein carrier.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, hapten-specific inducer cells are extremely rare. The data presented have, as well as studies by others (43)(44)(45), demonstrate that the vast majority of inducer-cell clones recognize hapten in association with a defined sequence of amino acids. The major consequence of this conjugate-specific recognition is a highly stringent requirement for stimulation: inducer cells can be stimulated only by a restricted set of proteins that carry the precise amino acid sequence of the original immunogen.…”
Section: Evidence For a Conserved Domain Of The I-a Molecule That Dirmentioning
confidence: 92%
“…In these studies, it was found that a change of one or two residues in the amino acid sequence of either A or MHC caused a loss of recognition (Keck, 1975;Zinkernagel, 1976;Maizels et al, 1980;Whitmore and Gooding, 1981;DeWaal et al, 1983;Townsend et al, 1983a, b;Berkower et al, 1984;Lin et al, 1984). Other studies have indicated that hapten-specific T-cells' are also capable of recognizing subtle differences in hapten structures (Gell and Silverstein, 1962;Silverstein ?nd Gell, 1962;Janeway et al, 1975Janeway et al, , 1976aLevy and Shearer, 1982;Rao et al, 1984).…”
Section: Paradoxical Aspects Of T·cell a Specificitymentioning
confidence: 99%